2013
DOI: 10.1038/ajg.2013.21
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Residue Breakfast Improves Patient Tolerance Without Impacting Quality of Low-Volume Colon Cleansing Prior to Colonoscopy: A Randomized Trial

Abstract: A low-residue breakfast on the day before elective colonoscopy does not compromise the overall quality of bowel preparation as compared with a standard clear-fluid diet and is likely to be preferred by patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(40 citation statements)
references
References 12 publications
1
39
0
Order By: Relevance
“…As greater acceptance of more effective regimens grows, liberalization of pre-procedure diets may be possible without sacrificing preparation adequacy. As compared to clear liquids alone, similar bowel cleansing scores have been demonstrated with a low-residue diet in conjunction with hyperosmotic bowel purgatives 6 7 8.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…As greater acceptance of more effective regimens grows, liberalization of pre-procedure diets may be possible without sacrificing preparation adequacy. As compared to clear liquids alone, similar bowel cleansing scores have been demonstrated with a low-residue diet in conjunction with hyperosmotic bowel purgatives 6 7 8.…”
Section: Introductionmentioning
confidence: 82%
“…Preparation adequacy was not an endpoint, and those assigned to the low-residue arm were required to strictly adhere to one of 3 specific menu offerings. A third study compared a low-residue diet to clears alone and used sodium picosulfate plus magnesium 6. All patients received bisacodyl for 2 days prior to beginning the purgative.…”
Section: Discussionmentioning
confidence: 99%
“…The adenoma detection rate and patient tolerance were similar in the two groups. Previous randomized controlled trials have compared a low‐residue with a clear liquid diet . According to Melicharkova et al .…”
Section: Discussionmentioning
confidence: 99%
“…14 They were all compared with clear-fluid diets. Purgatives varied from low-volume sodium phosphate 9 or sodium sulfate based, 14 medium-volume picosulfate, 13 or large volume PEG-based. [10][11][12] All showed that dietary liberalization did not compromise bowel preparation, and all but one showed improved tolerance and satisfaction.…”
Section: Discussionmentioning
confidence: 99%